a/ \(\left(8-5x\right)\left(x-2\right)+4\left(x-2\right)\left(x+1\right)+2\left(x-2\right)\left(x+2\right)+10\)
\(=8\left(x-2\right)-5x\left(x-2\right)+\left(4x-8\right)\left(x+1\right)+2\left(x^2-2^2\right)\)
\(=8x-16-5x^2+10x+4x\left(x+1\right)-8\left(x+1\right)+2x^2-2.2^2\)
\(=8x-16-5x^2+10x+4x^2+4x-8x-8+2x^2-8\)
\(=14x+x^2-32\)
b/ \(4\left(x-1\right)\left(x+5\right)-\left(x+2\right)\left(x+5\right)-3\left(x-1\right)\left(x+2\right)\)
\(=\left(x+5\right)\left[4\left(x-1\right)-\left(x+2\right)\right]-\left(3x-3\right)\left(x+2\right)\)
\(=\left(x+5\right)\left(4x-4-x-2\right)-\left[3x\left(x+2\right)-3\left(x+2\right)\right]\)
\(=\left(x+5\right)\left(3x-6\right)-\left(3x^2+6x-3x-6\right)\)
\(=x\left(3x-6\right)+5\left(3x-6\right)-\left(3x^2+3x-6\right)\)
\(=3x^2-6x+15x-30-3x^2-3x+6\)
\(=9x-24\)